2009
DOI: 10.1093/ejo/cjn082
|View full text |Cite
|
Sign up to set email alerts
|

Angular photogrammetric analysis of the soft tissue facial profile of Turkish adults

Abstract: One of the most important components of orthodontic diagnosis and treatment planning is the evaluation of the patient's soft tissue profile. The aim of this study was to develop angular photogrammetric standards for Class I Anatolian Turkish males and females. A random sample of 100 Turkish individuals (46 males and 54 females; ages 19-25 years) was obtained. The photographic set-up consisted of a tripod that held a 35 mm camera and a primary flash. The camera was used in its manual position and photographic r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
49
6
15

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(87 citation statements)
references
References 22 publications
17
49
6
15
Order By: Relevance
“…The average value of facial convexity angle (G-Sn-Pg) in the north Indian population is (168.54° ± 3.23° in males and 166.64° ± 4.09°in females) which is similar to the values given by Fernández-Riveiro 19 in white European population (168.2°± 4.96° in males and 167.0° ± 5.36° in females) and slightly less than the values given by Malkoç 21 in Turkish population (170.60° ± 6.15° in males and 168.78° ± 5.44° in females) and Anic´-Miloševic´2 0 in Caucasian population (168.78° ± 4.97°i n males and 169.05° ± 4.69° in females). It is observed that north Indian females have slightly more convex face compared to males also white European population has a slightly anterior divergent profile and hence larger angular measurements.…”
Section: Discussionsupporting
confidence: 69%
See 3 more Smart Citations
“…The average value of facial convexity angle (G-Sn-Pg) in the north Indian population is (168.54° ± 3.23° in males and 166.64° ± 4.09°in females) which is similar to the values given by Fernández-Riveiro 19 in white European population (168.2°± 4.96° in males and 167.0° ± 5.36° in females) and slightly less than the values given by Malkoç 21 in Turkish population (170.60° ± 6.15° in males and 168.78° ± 5.44° in females) and Anic´-Miloševic´2 0 in Caucasian population (168.78° ± 4.97°i n males and 169.05° ± 4.69° in females). It is observed that north Indian females have slightly more convex face compared to males also white European population has a slightly anterior divergent profile and hence larger angular measurements.…”
Section: Discussionsupporting
confidence: 69%
“…The mean value of nasofrontal angle (G-N-Prn) in the north Indian population is (136.71° ± 3.64° in males and 144.33° ± 1.75° in females) less in males and more in females as compared to the values given by both Fernández-Riveiro 19 Nasal tip angle (Cm-Sn/N-Prn), as evaluated in the north Indian adult population, does not show much difference between males and females, (75.09° ± 3.17° in males and 75.35° ± 3.08°i n females) which is more for males and less for females in comparison to the values given by Fernández-Riveiro 19 (72.6°± 9.04° in males and 76.28° ± 5.8° in females), whereas both the values are less than that of Anic´-Miloševic´2 0 (79.85° ± 6.36°i n males and 84.12° ± 5.20° in females) and Malkoç 21 (76.21°± 6.72° in males and 78.41° ± 9.17° in females). A sharper nasal tip in north Indian population is due to decreased nasolabial angle observed in north Indian population.…”
Section: Discussionmentioning
confidence: 51%
See 2 more Smart Citations
“…nın çalışmasında rastlanmaktadır (4,5). Her iki çalışmada da cinsiyetler arasında bir farklılık olmadığı rapor edilmiştir.…”
Section: Gereç Ve Yöntemunclassified